Discourse Analysis of Language Used in the Advertisiments of VIJU Company in Social Media Handles - Ahmad, Yusuf; Aliyu, Muhammad Mukhtar (STAIN Majene, 2023)
Advertisement plays a vital role in business activities and in recent years, social media has become most popularly platform of advertising product using varieties of styles. Therefore, this study examines the adverts of Viju Company in social media handles using a qualitative approach. Data for the study were collected from four adverts in Viju social media handles from 2017 to 2022. The data were analyzed based on graphological, phonetic, lexical, grammar and syntactic features. The findings reveal five colors used by Viju Company: Blue used in background to out shadow other features, red was used in the presentation of text to symbolize passion and energy, brown and milk were used in the bottle design of the advert to symbolize the color of the product, and white is used in the presentation of logo to symbolizes purity and wholesomeness. Then yellow is used to show the taste of the product. In addition, the findings reveal graphological features of the adverts: boldness, italics, and capitalization which are used as foregrounding. The study also reveals two phonetic features of the adverts: alliteration to create good emotional sound and assonance to achieve ‘remembrance’ effect. Additionally, the study observed four lexical features employed by Viju; Metonymy giving generality to the product, Euphemism and Hyperbole to target people’s mind, to increase shock, novelty, appearance or illustrative consequences. Metaphor is used to show the quality of the product. Furthermore, grammatical features: noun, verb and adjectives are used to complement the name and function of the product. Finally, for syntactic features, the study observed that only simple sentence was used in the Viju adverts. The paper highlights some implications and makes suggestions for further studies.